La calidad de vida y la calificación promedio de crédito en los cantones del Ecuador - Vallejo Díaz, Daniel Germánico (2021)
The credit score is a numerical indicator constructed to predict borrowers’ credit risk. It is used to set the interest rate a financial institution will charge for a loan. This study analyses the aggregate credit score for the cantons of Ecuador and its link with socioeconomic characteristics of such areas…